The converse would be If x² = 100 then x = -10
So essentially if the conditional statement is p → q then the converse is q → p (In essence, the converse of a conditional statement is formed by interchanging the hypothesis and the conclusion.)
ANSWER:
mean:47.8
mode:57
median:45
37, 38, 43, 45, 57, 57, 58
Answer:
-1 3/8
Step-by-step explanation:
Answer:
Step-by-step explanation:
There is no solution as you have two variables and only one equation. The best you can do is solve for one variable as a function of the other.
![7x^2+11y^2=40\\ \\ 11y^2=40-7x^2\\ \\ y^2=\frac{40-7x^2}{11}\\ \\ y=\sqrt{\frac{40-7x^2}{11}}](https://tex.z-dn.net/?f=7x%5E2%2B11y%5E2%3D40%5C%5C%20%5C%5C%2011y%5E2%3D40-7x%5E2%5C%5C%20%5C%5C%20y%5E2%3D%5Cfrac%7B40-7x%5E2%7D%7B11%7D%5C%5C%20%5C%5C%20y%3D%5Csqrt%7B%5Cfrac%7B40-7x%5E2%7D%7B11%7D%7D)